Dealing with DNA lesions: When one cell cycle is not enough. (June 2021) - Lezaja, Aleksandra; Altmeyer, Matthias
Abstract: Subversion of genome integrity fuels cellular adaptation and is a prerequisite for organismal evolution, yet genomic lesions are also the harmful driving force of cancer and other age-related human diseases. Genome integrity maintenance is inherently linked to genome organization and nuclear architecture, which are substantially remodeled during the cell cycle. Here we discuss recent findings on how actively dividing cells cope with endogenous genomic lesions that occur frequently at repetitive, heterochromatic, and late replicating regions as byproducts of genome duplication. We discuss how such lesions, rather than being resolved immediately when they occur, are dealt with in subsequent cell cycle phases, and even after mitotic cell division, and how this in turn affects genome organization, stability, and function. Graphical abstract: Image 1 Highlights: Repetitive, heterochromatic and late replicating regions are inherently fragile. Replication stress intermediates take more than one cell cycle to be resolved. Mitotic DNA synthesis precedes LLPS-mediated lesion compartmentalization in G1. Genomic lesions segregated over multiple cell generations shape cancer genomes.